Research methods in anthropology : qualitative and quantitative approaches . - Bernard, H. Russell (Lanham, MD : AltaMira Press, 2006)
Research Methods in Anthropology' is the standard textbook for methods courses in anthropology. This fourth edition contains all the useful methodological advice of previous editions and more: additional material on text analysis, an expanded section on sampling in field settings, and dozens of new examples.
Includes bibliographical references and indexes.
Keywords: Ethnology